Analogia entre propriedades de alguns polinômios ortogonais em uma e em várias variáveis - Souza, Mariana Aparecida Delfino de [UNESP] (2014)
By using the concepts about hypergeometric representation of orthogonal polynomials in one variable, Rodrigues formula and generating function, one can obtain orthogonal polynomials of several variables. In this work, we detail, speci cally, the Jacobi polynomials in two variables, the Legendre and Gegenbauer polynomials in several variables, by presenting their representations in terms of hypergeometric functions, by Rodrigues formulae, recurrence relations, orthogonality, among many others. These results are obtained by generalizing the concepts and properties of orthogonal polynomials in one variable